Robots have come to architecture to model, construct, fabricate and offer new approaches to create innovative designs, elements and structures. Issue 5 (12th August 2014) - Bloss, Richard
Abstract : Purpose: – The purpose of this paper is to review the dramatic entry of robotics into the field of architecture and construction. Design/methodology/approach: – Discussions with worldwide researchers in the field of applying robotics to architecture applications and attendance at the 2014 Rob-Arch Conference at Ann Arbor, Michigan. Findings: – Robots are enabling many new and innovative methodologies for architecture design and implementation, as well as construction. Practical implications: – Readers may be very surprised at the many tasks that robots are already tackling in enabling innovation to reach out to architectural design and implementation. Originality/value: – A review of a wide range of the applications of robots worldwide to architectural innovation.